Adaptive leadership among school principals and its relationship to the teaching self-efficacy of intermediate school teachers in public schools in Mecca from the point of view of educational supervisors - Abudahi, Salha Muhammad (Journal of Educational and Psychological Sciences, 2025)
The research aimed to assess the practice of transformational leadership among school principals in Makkah City, and measure the level of self-efficacy for teaching among middle school teachers from the perspective of supervisors. The sample included 164 educational supervisors. The findings revealed that middle school principals practice transformational leadership to a high degree, which enhances self-efficacy for teaching among teachers. The teachers are characterized by high self-efficacy for teaching in all its dimensions. There is a strong positive correlation between the practice of transformational leadership and self-efficacy for teaching. Years of experience and training courses also influence the practice of transformational leadership. The study recommended enhancing transformational leadership skills among middle school principals and building high self-efficacy for teaching among middle school teachers through training programs, continuous support, and creating a supportive school environment.
Keywords: Transformational leadership; Self-efficacy for teaching; educational supervisors